(untitled) (Research, Society and Development, 2022)
Objective: Analise and describe the clinical aspects and socio-demographics conditions of individuals with Parkinson’s Disease (PD) and clinical monitoring in the city of João Pessoa. Methodology: Descriptive study developed with 30 subjects of both genders, aged between 40 and 80 years, which were diagnosed with Idiopathic PD on all stages of Modified Hoehn and Yahr Scale (MHYS). The evaluation occurred by a semi-structured questionnaire, cognition tests and functional mobility. Results: The mean age found was 60,47 ± 7,57 years, where 71,3% are men, urban residents and average wage income of 2 to 3 minimum wages. The time of diagnosis was 82,5 ± 69,1 months, predominating the clinical mixed subtype. The calculated average on MMSE was 26,7 points. Participants presented motors disorders related to gait disfunctions, alleging freezing and an expressive number of falls. The most frequent non-motor symptoms were: sleep disorders (56,7%), cardiovascular disorders (36,7%) and gastrointestinal disorders (16,7%). Conclusion: based on this study results, was verified that the predominant socio-demographic profile are middle-aged individuals, married and male, that were classified between PD stages II and III, average time of diagnosis of 6 years and mixed clinical subtype. The social and cognitive level is consistent with the educational level of the sample. Also was observed the presence of important motor alterations related to gait disfunction, as well as non-motor PD symptoms.